An imagined region: environment, culture, and connectivity in modern Manchuria (Nuovi Autoritarismi e Democrazie: Diritto, Istituzioni, Società (NAD-DIS), 2021)
The toponym Manchuria has become controversial in China in recent years, even though its use has a long history in Europe and Asia. Detractors maintain that the place name poses a threat to China’s sense of unity, because it exaggerates the distinctiveness of Northeast China. This essay shows that in the last forty years in Italy, as in other Countries, Manchuria has been used less often than in the past. However, it is still a matter of discussion whether Northeast China can be considered a region, as the disputed toponym can suggest. The paper tries to address this question, through an analysis of the physical and cultural features of the area, as well as its economic connectivity, from the XVII Century to the beginning of the XX Century. The conclusions of this survey suggest that Manchuria did not present the typical features of a physical and human unit before han Chinese mass immigration and the completion of railways at the beginning of the XX Century.
Keywords: Manchuria; Region; Connectivity; Northeast; China